New siblings. (2nd February 2022) - Rawstrone, Annette
Abstract : Welcoming a new baby into your family is often an exciting time but can be daunting for young children. An only child will be going from having undivided attention to having to share it. Whatever the size of family, change can be difficult but you can support your child through the transition so they embrace, rather than fear, the new arrival.